Increasing the Solubility and Anti-Inflammatory Activity of Curcumin by Cocrystallization - Yudi Wicaksono; Kuni Zu’aimah Barikah; Amanda Della Yudatama; Havidhatul Maulia; Nuri; Dwi Setyawan (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2023)
Curcumin (CUR) is a polyphenolic compound that exhibits potent anti-inflammatory activity. However, only a tiny amount of CUR is absorbed during oral administration, which is because CUR is difficult to dissolve in water. The aim of the research was to increase the solubility of CUR through the cocrystallization technique using isonicotinamide coformer (INIC) by solvent evaporation. Cocrystal characterization was carried out using a powder X-ray diffractometer (PXRD), a differential scanning calorimeter (DSC), a Fourier transform infrared spectrometer (FTIR), and a scanning electron microscope (SEM). Solubility was evaluated using the shaking method, while the anti-inflammatory activity test was carried out using the carrageenan induced mouse leg edema method. The resulting CUR-INIC (1:1) cocrystal has a diffractogram with new diffraction peaks of 2theta at 15.00, 16.22, and 22.89◦ compared to the individual diffractograms of CUR and INIC. In the cocrystal, CUR and INIC form intermolecular interactions of hydrogen bonds, resulting in a new solid phase with a melting point of 160.1◦C. The solubility of the CUR-INIC cocrystal in water was 73.1±0.23 ug/mL, which increased 14 times compared to the solubility of initial CUR, which was only 5.05±0.07 ug/mL. The CUR-INIC cocrystal showed a percentage of edema inhibition in mice (5 hours) 130% more potent than that of initial CUR. Therefore, CUR-INIC cocrystals can be used to improve CUR solubility to obtain more excellent anti-inflammatory effects.